Exchange of private demand information by simultaneous signaling - Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
As is well-known from the literature on oligopolistic competition with incomplete information, firms have an incentive to share private demand information. However, by assuming verifiability of demand data, these models ignore the possibility of strategic misinformation. We show that if firms can send misleading demand information, they will do so. Furthermore, we derive a costly signaling mechanism implementing demand revelation, even without verifiability. For the case of a gamma distribution of the firms' demand variables, we prove that the expected gross gains from information revelation exceed the expected cost of signaling if the skewness of the distribution is sufficiently large and the products are sufficiently differentiated.
urn:nbn:de:bsz:21-opus-57395
Keywords: C73; D82; L13; 330; Information sharing; simultaneous signaling; demand uncertainty